The Effectiveness of Narrative Pre-Experiences for Creating Context in Military Training. (August 2013) - Bowers, Clint A.; Serge, Stephen; Blair, Lucas; Cannon-Bowers, Janis; Joyce, Rachel; Boshnack, James
Trainers need to identify effective, low-cost training experiences for today's military workforce to meet the increasing demands of today's warfighting environment. Although low-fidelity simulations have been demonstrated to be effective in this regard, research has demonstrated that specially tailored pre-experiences can increase the effectiveness of these simulations. Unfortunately, the cost of these pre-experiences negates the cost benefits of the simulations that they improve. In this article, we describe a study to evaluate the effectiveness of a lower cost pre-experience. The results are discussed in the context of future directions for research.